A new linear phenyloxazole-benzothiadiazole luminophore: crystal growth, structure and fluorescence properties - Postnikov, Valery A; Sorokina, Natalia I; Kulishov, Artem A; Lyasnikova, Maria S; Sorokin, Timofei A; Freidzon, Alexandra Ya; Stepko, Anastasia S; Borshchev, Oleg V; Skorotetsky, Maxim S; Surin, Nikolay M; Svidchenko, Evgeniya A; Ponomarenko, Sergey A (Acta crystallographica Section B, Structural science, crystal engineering and materials, 2022)
A new linear luminophore consisting of five conjugated units of oxazole, phenylene and a central benzothiadiazole fragment, 4,7-bis[4-(1,3-oxazol-5-yl)phenyl]-2,1,3-benzothiadiazole, has been synthesized and characterized. Needle-like single-crystal samples up to 10 mm in length were obtained by physical vapor transport. The crystal structure was determined at 95 K and 293 K using single-crystal X-ray diffraction. With decreasing temperature, the space group P2 /n does not change, but the unit-cell volume of the crystal decreases. The presence of intra- and intermolecular hydrogen bonds was established. Melting parameters (T = 305.5°C, ΔH = 52.2 kJ mol ) and the presence of a liquid-crystalline mesophase (T = 336.3°C, ΔH = 1.4 kJ mol ) were determined by differential scanning calorimetry and in situ thermal polarization optical microscopy studies. The presence of linear chains of hydrogen bonds ensures high stability of the crystal structure in a wide temperature range. The luminophore is characterized by a large Stokes shift (5120-5670 cm ) and a high quantum yield of fluorescence, reaching 96% in solutions (λ = 517 nm) and 27% in thin crystalline films (λ = 529 nm). The calculated absorption and emission spectra are in good agreement with the experimental data. Because of the excellent optical properties and high thermal stability, the new linear luminophore has great potential for application in organic photonics and optoelectronic devices.